Dukungan Emosional Keluarga dengan Depresi Lansia di Gereja Santo Yakobus Kelapa Gading - Maria, Stephanie Ditha; Ernawati, . (E-Jurnal Medika Udayana, 2025)
Background : Depression is the most common mental disorder characterized by persistent sadness and lack of interest in daily activities. This condition requires special attention as it can be life-threatening. Depression can be caused by a variety of factors such as biological, social, and psychological. One of the psychological factors that influence depression is family emotional support. Family emotional support can be provided by showing patience and encouraging the elderly. Objective : This study aims to see the relationship between family emotional support and depression in the elderly. Methods : The research was conducted using a cross-sectional design, and non-random sampling, and 118 elderly respondents were selected from the Santo Yakobus Church Kelapa Gading. Respondents filled out the questionnaire directly and through the g-form. Results : The statistical test used was Fisher's Exact and the results of this study showed that there was no significant relationship between family emotional support and depression in the elderly with a p-value = 0.884> 0.05. However, elderly people who do not get emotional support tend to experience depression 1.43 times compared to those who get support (PRR 1.43). Conclusion : There is no significant relationship between family emotional support and depression in the elderly. Keywords : family emotional support ., elderly., depression